2014
DOI: 10.1002/da.22278
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Major Depression and Cerebrospinal Fluid Free Gamma-Aminobutyric Acid

Abstract: Background Low gamma-aminobutyric acid (GABA) is implicated in both anxiety and depression pathophysiology. They are often comorbid, but most clinical studies have not examined these relationships separately. We investigated the relationship of cerebrospinal fluid (CSF) free GABA to the anxiety and depression components of a major depressive episode (MDE) and to monoamine systems. Methods and Materials Patients with a DSM-IV major depressive episode (N = 167: 130 major depressive disorder; 37 bipolar disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 57 publications
7
54
0
1
Order By: Relevance
“…The observed increase in GABA was also seen in nonresponders, suggesting that GABA increase may contribute to the antidepressant mechanism of TMS, but this association was not causal. Levels of GABA are low in the depressed brain, supported by convergent evidence from CSF samples, 25 GABAergic neuronal density 26 and GAD67 expression 27 in postmortem brains. Prior MRS studies revealed GABA reductions in depressed individuals compared with healthy controls, 11,28 with more pronounced MPFC reductions in a treatment-refractory subgroup.…”
Section: Discussionmentioning
confidence: 85%
“…The observed increase in GABA was also seen in nonresponders, suggesting that GABA increase may contribute to the antidepressant mechanism of TMS, but this association was not causal. Levels of GABA are low in the depressed brain, supported by convergent evidence from CSF samples, 25 GABAergic neuronal density 26 and GAD67 expression 27 in postmortem brains. Prior MRS studies revealed GABA reductions in depressed individuals compared with healthy controls, 11,28 with more pronounced MPFC reductions in a treatment-refractory subgroup.…”
Section: Discussionmentioning
confidence: 85%
“…Our search identified 45 studies: 26 studies for the comparison of patients with current MDE versus healthy controls, [8][9][10][11][12][13][14][15][16][17][18]30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] 12 studies for the comparison of patients with current MDE before treatment versus after treatment, 12,20,23,25,26,28,36,43,[47][48][49][50] and 11 for the comparison of euthymic patients and controls. 18,[21][22][23]27,29,38,[51][52][53][54] Figure 1 depicts the study selection proce...…”
Section: Resultsmentioning
confidence: 99%
“…GABA A receptors are widely distributed in the brain and are the primary channels through which GABA inhibits the excitability of neurons in the central nervous system (24,25). Abnormalities in GABA function have been postulated for many years in bipolar disorder and are supported by the observation of decreased CSF GABA in bipolar patients (26), as well as alterations in GABA subunit ratios in the postmortem brain (27). Positive allosteric modulators of GABA A receptors (benzodiazepines) are used adjunctively in the treatment of mania, a key aspect of BD.…”
Section: Discussionmentioning
confidence: 99%